Diagnostic value of 18F-FDG PET/CT in paediatric neuroblastoma: comparison with 131I-MIBG scintigraphy. Issue 10 (October 2015) - Dhull, Varun S.; Sharma, Punit; Patel, Chetan; Kundu, Parveen; Agarwala, Sandeep; Bakhshi, Sameer; Bhatnagar, Veereshwar; Bal, Chandrasekhar; Kumar, Rakesh
Abstract : Purpose: The aim of the study was to evaluate the diagnostic value of fluorine-18 fluorodeoxyglucose ( 18 F-FDG) PET/computed tomography (CT) in paediatric patients with neuroblastoma (NB) and compare the results with iodine-131 metaiodobenzylguanidine ( 131 I-MIBG) scintigraphy. Methods: Data on 40 paediatric patients (age, 5.5±5.6 years; male, 32; female, eight) with histopathologically proven NB who underwent 18 F-FDG PET/CT (staging, 21 patients; restaging/response monitoring, 19 patients) were retrospectively evaluated. 131 I-MIBG scintigraphy data were available for 28/40 patients (median interval, 15 days; staging, 20 patients; restaging/response monitoring, eight patients). 131 I-MIBG scintigraphy and 18 F-FDG PET/CT images were evaluated by two nuclear medicine physicians in consensus and in separate sessions. Histopathology ( n =50 lesions) and/or clinical/imaging follow-up ( n =90 lesions) data were taken as the reference standard. Results: Patient-wise sensitivity, specificity, positive-predictive value, negative-predictive value and accuracy of 18 F-FDG PET/CT were 100, 50, 91.89, 100 and 92.50%, respectively. A total of 140 lesions (primary, 37; lymph node, 31; bone, 50; bone marrow, 15; and others, seven) were detected on PET/CT. In 28 patients undergoing both imaging studies, the sensitivity, specificity, positive-predictive value, negative-predictive value and accuracy of 18 F-FDG PET/CT were 100, 60, 92, 100 and 92.80%, respectively, and those of 131 I-MIBG were 95.65, 60, 91.67, 75 and 89.20%, respectively. In these 28 patients, PET/CT detected 107 lesions (primary, 25; lymph node, 22; bone/bone marrow, 56; and others, four) and 131 I-MIBG scintigraphy detected 74 lesions (primary, 24; lymph node, five; and bone/bone marrow, 45). On a patient-based comparison there was no significant difference between 18 F-FDG PET/CT and 131 I-MIBG ( P =1.000), but 18 F-FDG PET/CT was superior to 131 I-MIBG on a lesion-based comparison ( P <0.0001). Although no difference was noted for primary lesions ( P =1.000), PET/CT was superior to 131 I-MIBG scintigraphy for the detection of lymph nodal ( P =0.001) and bone/bone marrow lesions ( P =0.007). Conclusion: 18 F-FDG PET/CT shows high accuracy in paediatric patients with NB and demonstrates more lesions as compared with 131 I-MIBG scintigraphy.